THE IMPACT OF CHARISMATIC LEADERSHIP ON THE ORGANIZATION - Latif, Muhaemin (Journal of Islam and Science, 2016)
This paper is trying to elaborate the concept of charismatic leadership, the characteristics, the role and implication to the organization. It is believed that charismatic leadership has large contribution to the development of organization. It can develop creativity and critical thinking to the followers. However, charismatic leadership also poses negative effect in relation to the followers. The followers are vulnerable in blind fanaticism which leads to self-sacrifice. The leaders are often more arrogance and not aware about social responsibilities. In general, charismatic leadership is a good style among the modes of organization, particularly if it combined with transformational leadership. This is relevant and have been applied  at UIN Alauddin Makassar.